Necrotizing enterocolitis: Bench to bedside approaches and advancing our understanding of disease pathogenesis - Singh, Dhirendra K.; Miller, Claire M.; Orgel, Kelly A.; Dave, Mili; Mackay, Stephen; Good, Misty (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is a devastating, multifactorial disease mainly affecting the intestine of premature infants. Recent discoveries have significantly enhanced our understanding of risk factors, as well as, cellular and genetic mechanisms of this complex disease. Despite these advancements, no essential, single risk factor, nor the mechanism by which each risk factor affects NEC has been elucidated. Nonetheless, recent research indicates that maternal factors, antibiotic exposure, feeding, hypoxia, and altered gut microbiota pose a threat to the underdeveloped immunity of preterm infants. Here we review predisposing factors, status of unwarranted immune responses, and microbial pathogenesis in NEC based on currently available scientific evidence. We additionally discuss novel techniques and models used to study NEC and how this research translates from the bench to the bedside into potential treatment strategies.